The Relationship between Perception of Organizational Politics, Emotional Intelligence and Work Outcomes: Empirical Evidence from Banking Sector of Pakistan (Global Journal of Human-Social Science, 2014)
Emotional intelligence and organizational politics are an essential part of organizational lifespan and a politically charged organization is discouraging to work in. The purpose of this study is to examine the relationship between perceived organizational politics and emotional intelligence and work outcomes. The major objective is to explore the role of emotion in organizational politics in the banking sector of Pakistan. The self-designed questionnaire was used for data collection from 105 employees who are working at managerial level and non managerial level in banking sector. The findings of the study showed the positive relationship between emotional intelligence and perception of politics and these findings help the top management of banking sector to know the how emotion and organizational politics affect on the work out comes of the employees. The finding will also be useful in designing and implementing the strategic management decisions.
Keywords: emotional intelligence; organizational politics; work outcomes